Observations of the Crustal Mini-magnetopause Reconnection at Mars - Xinzhi Qiu; Yiqun Yu; Jing Wang; Lihui Chai; Fan Gong; Longhui Liu; Jinbin Cao (The Astrophysical Journal)
Magnetopause reconnection is a fundamental mechanism for mass and energy transfer in terrestrial planetary systems. Unlike Earth, Mars lacks a global magnetic field and instead has localized crustal magnetic fields, which can create structures morphologically similar to a scaled-down intrinsic magnetosphere, potentially forming mini-magnetospheres. In this study, we investigate reconnection in Martian mini-magnetospheres on the dayside, analyzing key characteristics of the reconnecting current sheet, and the associated ion escape rate, and comparing these features to reconnection events at the induced magnetopause documented in previous studies. Our observations reveal that, in the subsolar region, the thickness of the Martian mini-magnetopause is comparable to the upstream proton inertial length and the convective gyroradius of the magnetosheath solar wind. However, at higher solar zenith angles, this thickness increases to several times these characteristic lengths. Reconnection-driven ion escape rates at the induced magnetopause are at least 1 order of magnitude greater than those associated with mini-magnetopause reconnection. These findings provide new insights into reconnection processes at Martian boundary layers.